2022
DOI: 10.1186/s12964-022-00921-4
|View full text |Cite
|
Sign up to set email alerts
|

SENP1 regulates the transformation of lung resident mesenchymal stem cells and is associated with idiopathic pulmonary fibrosis progression

Abstract: Background Lung resident mesenchymal stem cells (LR-MSCs) play an important role in idiopathic pulmonary fibrosis (IPF) by transforming into myofibroblasts, thereby losing their repair ability. Evidence suggests that key proteins of multiple signaling pathways are involved in myofibroblast differentiation of LR-MSCs, such as β-Catenin and GLI family zinc finger 1 (GLI1). These proteins are regulated by SUMO (small ubiquitin-like modifier) modification, which is a post-translational modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In addition, ER stress has been identified within the IPF lung and has recently been linked to the differentiation of LR-MSCs to myofibroblasts, with the C/EBP homologous protein (CHOP) noted as being integral to this process. 63 …”
Section: Lung Resident Mscs In Pathogenesis Of Chronic Lung Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ER stress has been identified within the IPF lung and has recently been linked to the differentiation of LR-MSCs to myofibroblasts, with the C/EBP homologous protein (CHOP) noted as being integral to this process. 63 …”
Section: Lung Resident Mscs In Pathogenesis Of Chronic Lung Diseasesmentioning
confidence: 99%
“… 39 Overexpression of the deSUMOylation enzyme SENP1 was observed in LR-MSCs differentiating into myofibroblasts. 63 Downregulation of SENP1 could reverse this differentiation by promoting SUMOylation of Wnt and HH proteins, and enhancing the degradation of β-catenin and GLI1. The findings from these studies link HH and Wnt signaling with the differentiation and fibrotic effects of LR-MSCs.…”
Section: Lung Resident Mscs In Pathogenesis Of Chronic Lung Diseasesmentioning
confidence: 99%
“…Although evidence has suggested that LRMPC actively contribute to IPF, evidence in animal models suggests that LRMSC could be involved in pulmonary fibrosis as a consequence of MSC exhaustion [ 16 ] and thereby limiting the regeneration of alveolar epithelium, and/or because they actively contribute to the dysregulated repair mechanism by differentiating into myofibroblasts [ 17 ]. Other studies conducted on LRMSC from lung damage animal models showed that LRMSC are able to differentiate into myofibroblasts through the activation of hedgehog and Wnt/B-catenin signaling [ 18 , 19 ] and suggested that they could be a major source of myofibroblasts, thereby actively contributing to pulmonary fibrosis progression [ 20 , 21 , 22 , 23 , 24 ]. In a study with human LRMSC involving IPF patients [ 25 ], the authors showed that IPF LRMSC displayed a higher expression of genes involved in inflammation, oxidative stress, hypoxia, and ECM pathway than control LRMSC and, in co-culture with control MSC or fibroblasts, induced a pathological phenotype on the surrounding cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that SUMOylation and deSUMOylation play a role in the development of fibrosis in different organs, including the heart, liver, and kidney(Liu et al 2017 ; Zhao et al 2021 ; Wang et al 2018 ; Sun et al 2022 ). A recent study revealed that significantly higher expression of SUMO1, SUMO2, and UBC9 in total lung tissue of IPF patients compared to healthy individuals, accompanied by downregulation of SENP1(Yu et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been determined that Lung-resident mesenchymal stem cells (LR-MSCs) may be a source of myofibroblasts, accelerating the development of IPF(Inui et al 2021 ; Yang et al 2021a ). Overexpression of SENP1 in LR-MSCs can stimulate the Wingless/Integrated (WNT)/β-catenin and Hedgehog/Glioma-associated oncogene homolog (GLI) signaling pathways by deSUMOylation of critical proteins, and encourage the transformation of LR-MSCs into myofibroblasts, exacerbating the development of pulmonary fibrosis(Sun et al 2022 ). As a result, SENP1 has emerged as a promising therapeutic target for the restoration of LR-MSC physiological functions and the treatment of pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%